The functions of role-playing games : how participants create community, solve problems and explore identity - Bowman, Sarah Lynne (Jefferson, N.C. : McFarland & Co., 2010)
'This analytical study takes a deeper look at the world of role-playing games, providing a theoretical framework for understanding their more acute psychological and sociological functions. The study also offers a detailed participant-observer ethnography on role-playing games, featuring insightful interviews with 19 participants of table-top, live action and virtual role-playing games'--Provided by publisher.
Includes bibliographical references (p. 197-202) and index.
Keywords: Fantasy games -- Social aspects; Role playing -- Social aspects